Plumes of Deep-Sea Mining: What Do We Know? - Livia Ermakova; Georgy Cherkashov (International Marine Minerals Society, 2018)
Active development of the exploration and further exploitation of deep-sea minerals requires special emphasis on the protection of the marine environment. The complexity of this subject lies in the fact that potential impact and effects of future mining activity are not completely known. One of the main sources of potential impact near the seafloor, as it expected, would be a generation of sediment plumes, their dispersion and redeposition of sediment. Meanwhile, their dimensions, rates of dispersion and redeposition are a big issue. Other plumes are expected in the surface layer as a result of discharges of processing waters and particles after sorting on board of mining vessel, and their features are also not clear. At the same time, understanding of these aspects would be crucial for definition of environment impact area, delineation and designation of different types of protected areas (Areas of Particular Environmental Interest, Impact and Preservation Reference Zones) and future assessment of environmental impacts. Attempts to address these issues demonstrated wide variations between the data of field experiments on the one hand and the results of analytical and numerical models on the other. According to in situ measurements, plumes were detected at a distance vary from one to less than 20 km [e.g., Burns et al., 1980; Sharma et al., 2001; Nautilus Minerals, 2008 etc.], whilst some models show results up to 100 km [Rolinski S. et al., 2001] and more. It seemed that results of in-situ experiments are preferable, but they were not many indeed. However, these data were used in different investigations rather widely, but their focus, as far as we know, was not on the matters related directly with plumes.